Utilization of maternal health-care services by tribal women in Kerala - Jinu Annie Jose, Sonali Sarkar, S. Ganesh Kumar and Sitanshu Sekhar Kar (Journal of Natural Science, Biology and Medicine, 2014)
Background: The coverage of maternal care services among the tribal women in Kerala is better as compared to other states in India. Aim: This study was done to identify the factors contributing to better coverage of maternal care services among the tribal women in Kerala and to study the reasons for remaining differences that exists in utilization of services between tribal and non-tribal pregnant women. Settings and Design: This was a descriptive cum qualitative study conducted in Thariode Gramapanchayat in the Wayanad district of Kerala. Materials and Methods: Among all women who had registered their pregnancies in the 5 sub-centres under CHC Thariode and had delivered between September 2009 and October 2010, equal numbers of tribal and non-tribal ante-natal women, 35 each were interviewed in-depth using a semi-structured questionnaire. Statistical Analysis Used: Quantitative data was analysed using SPSS Version 16.0. Content analysis was done for qualitative data. Results: The determinants of utilization in tribal women were general awareness, affordability, accessibility and quality of services along with motivation by health workers. Among tribal antenatal women, 85% utilized maternal health care facilities fully compared to 100% among non-tribal women. Lower levels of education and lack of transport facilities were prime factors contributing to under utilization by tribal women. Conclusions: Affordable, accessible and good quality of services in the public health system in Kerala and motivation by health workers were important contributing factors for better utilization of maternal care service